Systemic Steroid Application Caused Sudden Death of a Patient with Sudden Deafness - Eriko Ogino-Nishimura; Takayuki Nakagawa; Ichiro Tateya; Harukazu Hiraumi; Juichi Ito (Case Reports in Otolaryngology)
A 63-year-old man, who was diagnosed with sudden sensorineural hearing loss (SSHL), showed severe hypertension 10 hours after prednisolone administration. Subsequently, the patient suddenly died due to pulmonary edema. The autopsy indicated a pheochromocytoma in the right adrenal gland, and the cause of death was determined to be a pheochromocytoma crisis induced by systemic administration of prednisolone. Pheochromocytoma crisis is a life-threatening condition and can result from the use of corticosteroids. Physicians should consider the risk of a pheochromocytoma crisis due to systemic corticosteroids in the treatment of patients with sudden sensorineural hearing loss.